Clinical picture: SDHD paraganglioma presenting with syncope - LaChance, David P. (Clin Case Rep, 2020)
Described is an atypical presentation of a rare condition. It highlights the importance of thorough algorithm of medical and family history, physical examination, appropriate investigations, and perioperative workup and for surgery. The report demonstrates how even such very rare nonsecreting paragangliomas can be secondary to mass effects.